Transformational Leadership’s Impact on Enhancing Employee Performance in Medan MSME Sector - Amirulsyah; Safrida; Muhammad Endang Asmara (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
As the backbone of Medan’s economy, Micro, Small, and Medium Enterprises (MSMEs) play a central role in sustaining livelihoods and driving regional growth. However, to overcome persistent challenges such as limited capital, market access, and human resource constraints, effective leadership becomes a critical factor for ensuring resilience and long-term sustainability. This study aims to analyze the role of transformational leadership in improving employee performance in the MSMEs sector in Medan City. Using a qualitative approach through case studies on several MSMEs such as Serumpun Deli, Animers Craft, Dian Kitchen, and Gallery Fika, this study found that the four main dimensions of transformational leadership, ideal influence, inspirational motivation, intellectual stimulation, and individual attention are able to increase employee loyalty, motivation, and productivity. These findings reinforce the theories of Bass and Avolio and show that the application of transformational leadership is effective in building an innovative and collaborative work culture. This study recommends strengthening leadership capacity in MSME actors as a strategy to increase competitiveness in the era of digital transformation.